The pygidial gland secretion of Laemostenus punctatus (Coleoptera, Carabidae): a source of natural agents with antimicrobial, anti-adhesive, and anti-invasive activities - Nenadić, Marija; Stojković, Dejan; Soković, Marina; Ćirić, Ana; Dimkić, Ivica; Janakiev, Tamara; Vesović, Nikola; Vujisić, Ljubodrag; Todosijević, Marina; Stanković, Saša S.; Ćurčić, Nina B.; Milinčić, Uroš; et al. (Frontiers in Ecology and Evolution, 2023)
In the present study, we investigated in vitro the antimicrobial activity of the pygidial gland secretion of the guanophilic ground beetle Laemostenus (Pristonychus) punctatus (Dejean, 1828) and some of its chemicals against resistant and non-resistant bacteria and Candida species, the synergistic and additive potential of combinations of selected chemicals and antimicrobial drugs against resistant bacterial and fungal strains, anti-adhesive and anti-invasive potential of the secretion and formic acid alone and in selected combinations with antimicrobial drugs against methicillin-resistant Staphylococcus aureus (MRSA) towards spontaneously immortalized human keratinocyte cell line (HaCaT cells). In addition, we examined the antiproliferative activity of the secretion and formic acid in vitro. The tested secretion and the standards of formic and oleic acids possessed a significant level of antimicrobial potential against all tested strains (P < 0.05). The isolate from guano Pseudomonas monteilii showed the highest resistance to the secretion and formic acid, while MRSA achieved a significantly high level of susceptibility to all agents tested, particularly to the combinations of formic acid and antibiotics, but at the same time showed a certain level of resistance to the antibiotics tested individually. Candida albicans and C. tropicalis were found to be the most sensitive fungal strains to the secretion. Formic acid (MIC 0.0005 mg/mL) and gentamicin (MIC 0.0010 mg/mL) in the mixture achieved synergistic antibacterial activity against MRSA (FICI = 0.5, P < 0.05). The combination of formic acid, gentamicin and ampicillin accomplished an additive effect against this resistant bacterial strain (FICI = 1.5, P < 0.05). The secretion achieved a better inhibitory effect on the adhesion ability of MRSA towards HaCaT cells compared to formic acid alone, while formic acid showed better results regarding the invasion (P < 0.001). The combinations of gentamicin and ampicillin, as well as of formic acid and gentamicin and ampicillin achieved similar anti-adhesive and anti-invasive effects, with a slight advantage of formic acid and antibiotics in combination (P < 0.001). The secretion and formic acid were found to be non-toxic to HaCaT cells in vitro (IC50 ≥ 401 µg/mL).